Feeding habits shape infection levels by plerocercoids of the tapeworm Triaenophorus crassus in muscle of a sympatric pair of whitefish in an oligotrophic lake - Kashinskaya, Elena N.; Vlasenko, Pavel G.; Bochkarev, N. A.; Andree, Karl B.; Solovyev, Mikhail M. (Journal of Helminthology, 2021)
Lake Teletskoye (West Siberia, Russia) is inhabited by a sympatric pair of whitefish, with each member of the pair being characterized by different feeding habits. Coregonus lavaretus pidschian (Gmelin, 1789) is a large ‘benthivorous’ form, while C. l. pravdinellus (Dulkeit,1949) is a small ‘planktivorous’ form. Fish were collected from the end of August to the middle of September in 2017 and 2019–2020 in the north part of Lake Teletskoye. For the ‘benthivorous’ form the prevalence, intensity and abundance of T. crassus ranged from 22.4% to 51.9%, 1.9–2.8 and 0.4–1.3, respectively, whereas the same indices for the ‘planktivorous’ form ranged from 94.7% to 97.5%, 4.2–4.8 and 4.0–4.7, respectively. The level of prevalence of infection and abundance of T. crassus in muscle was relatively stable among studied years for both forms. The level of prevalence was higher in the years 2019 and 2020 than in 2017 for the ‘benthivorous’ form, whereas for the ‘planktivorous’ form this index did not change during the studied years. For the first time, a partial sequencing of the cox1 gene (593 bp) for T. crassus was sequenced. All 15 plerocercoids of T. crassus were represented by four haplotypes.